2019
DOI: 10.3390/ijerph16132360
|View full text |Cite
|
Sign up to set email alerts
|

Association between Level of Empathy, Attitude towards Physical Education and Victimization in Adolescents: A Multi-Group Structural Equation Analysis

Abstract: Currently, there is a problem related to violence and tolerance towards violence, and the levels of empathy of the subjects can affect this, in addition to the practice of physical activity. The present study sought to define and contrast an explanatory model of victimization, empathy and attitude towards physical education, and to analyze the existing relationships between these variables as a function of engagement with physical activity. A total of 2388 adolescents from Spain participated in this research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…When an individual can experience other’s feelings and adopt other’s perspectives, he or she is likely to avoid causing any harm ( van Hazebroek et al, 2017 ). Indeed, it has been suggested that the levels of empathy and the development of aggressive and violent behaviors are highly correlated – lower levels of empathy increase the development of manifest and relational aggressiveness, while high levels of empathy decrease the emergence of violent acts ( van Hazebroek et al, 2017 ; Arufe-Giraldez et al, 2019 ). Using structural equation modeling analysis, a recent investigation on a cohort of 734 school children aged 10–12 years demonstrated a negative relationship between affective empathy and relational aggression.…”
Section: Musical Training Boosts Empathy and Prosocial Behaviorsmentioning
confidence: 99%
“…When an individual can experience other’s feelings and adopt other’s perspectives, he or she is likely to avoid causing any harm ( van Hazebroek et al, 2017 ). Indeed, it has been suggested that the levels of empathy and the development of aggressive and violent behaviors are highly correlated – lower levels of empathy increase the development of manifest and relational aggressiveness, while high levels of empathy decrease the emergence of violent acts ( van Hazebroek et al, 2017 ; Arufe-Giraldez et al, 2019 ). Using structural equation modeling analysis, a recent investigation on a cohort of 734 school children aged 10–12 years demonstrated a negative relationship between affective empathy and relational aggression.…”
Section: Musical Training Boosts Empathy and Prosocial Behaviorsmentioning
confidence: 99%
“…It can be said that attitudes towards Physical Education and Sports lessons are effective as a predictor of empathy subdimensions in sports. It can be said that the theoretical and practical dimensions of the courses related to sports education in the curriculum of the Physical Education and Sports courses will contribute to the empathy in the sports environment together with the positive attitude (Arufe-Giráldez et al, 2019). On the other hand, it can be said that the values such as cooperation, cooperation and respect, which are included in the game philosophy of the game activities in the Physical Education and Sports course, can be an effective factor on the empathic behavior towards the coach, his/her teammates, referees and other stakeholders in the sports environment (Dorak & Vurgun, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked whether or not they engaged in more than 3 h of physical activity a week (do you engage in more than 3 h of physical activity outside of school hours?). In this case, this question is used to check whether the participants are physically active or not [ 23 ]. Participating Physical Education teachers measured and weighed participants for subsequent calculation of BMI.…”
Section: Methodsmentioning
confidence: 99%